Coping with the crisis: managing social security in uncertain times (Geneva, 2012)
"The ISSA Crisis Monitor project was tasked with monitoring the impact of the financial and economic crisis on social security and subsequent responses by social security administrations around the world. This report draws together the analysis from this project. "